2020
DOI: 10.3390/ijms21217864
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a Circular RNA–microRNA–mRNA-Signaling Regulatory Axis that Modulates Stemness Properties of Cancer Stem Cell Populations in Colorectal Cancer Spheroid Cells

Abstract: Spheroidal cancer cell cultures have been used to enrich cancer stem cells (CSC), which are thought to contribute to important clinical features of tumors. This study aimed to map the regulatory networks driven by circular RNAs (circRNAs) in CSC-enriched colorectal cancer (CRC) spheroid cells. The spheroid cells established from two CRC cell lines acquired stemness properties in pluripotency gene expression and multi-lineage differentiation capacity. Genome-wide sequencing identified 1503 and 636 circRNAs spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 101 publications
0
21
0
Order By: Relevance
“…Due to the similarities between ALK7, ALK4, and ALK5 discussed above, over-expression of ALK7 will result in activation of pathways that are common to all these receptors, hence not possible to exclusively ascribe to endogenously expressed ALK7. Several microRNAs with effects on proliferation, apoptosis, or invasion of cancer cells have also been reported to target the mRNA encoding ALK7, including miR-382 and miR-548c-3p [53], miR-23b [43], miR-454 [54], and miR-376c [55]. However, these microRNAs have multiple target genes, including other TGF-b superfamily receptors [56], and hence, the specific contribution of ALK7 to the effects reported following microRNA overexpression or knock-down remains unclear.…”
Section: Alk7: An Activin Receptor In Endocrine Tissuesmentioning
confidence: 99%
“…Due to the similarities between ALK7, ALK4, and ALK5 discussed above, over-expression of ALK7 will result in activation of pathways that are common to all these receptors, hence not possible to exclusively ascribe to endogenously expressed ALK7. Several microRNAs with effects on proliferation, apoptosis, or invasion of cancer cells have also been reported to target the mRNA encoding ALK7, including miR-382 and miR-548c-3p [53], miR-23b [43], miR-454 [54], and miR-376c [55]. However, these microRNAs have multiple target genes, including other TGF-b superfamily receptors [56], and hence, the specific contribution of ALK7 to the effects reported following microRNA overexpression or knock-down remains unclear.…”
Section: Alk7: An Activin Receptor In Endocrine Tissuesmentioning
confidence: 99%
“…In chronic lymphocytic leukemia (CLL) cells, circ-CBFB indirectly upregulates Fzd3 expression and downstream Wnt/β-catenin signaling by inhibiting miR-607 ( Xia et al, 2018 ). Similar mechanisms were observed in CRC spheroid cells where circ_0082096 and circ_006631 upregulate Fzd3 expression by inhibiting miR382, miR-579, miR-224, and miR-548c ( Rengganaten et al, 2020 ). CircRNA_100290 also influences colorectal carcinoma (CRC) by inhibiting miR-516b in CRC cells, indirectly upregulating Fzd4 and the Wnt/β-catenin pathway ( Fang et al, 2018 ).…”
Section: Circular Rnamentioning
confidence: 53%
“…Of these, the top three with the highest degree score of DEcircRNAs included hsa_circ_0031583, hsa_circ_0008197, and hsa_circ_0036627. A ceRNA network mediated via DEcircRNAs modulated histological classi cations and gastric cancer progression (29) and the stemness properties of colorectal cancer stem cells (30). No report has shown that hsa_circ_0031583, hsa_circ_0008197, and hsa_circ_0036627 affected tumor progression.…”
Section: Discussionmentioning
confidence: 99%